PENERAPAN MODEL PEMBELAJARAN COURSE REVIEW HORAY TARI NO TATEMA MBOLA MELALUI MEDIA KARTU POS UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN DI SMP DARUSSALAM MEDAN - Rina Devi Yanti Siregar; Tuti - Rahayu (Universitas Negeri Medan, 2021)
ABSTRACT, This study aims to describe the application of the Course Review Horay learning model in the dance appreciation learning no tatema mbola through postcard media to the effectiveness of student learning in Medan Darussalam Middle School. The theory used in this research is the theory of Course Review Horay models from Imas Kurniasih and Berlin Sani 2016, and the theory of postcard learning media Rudi Susilana and Cepi Riyana 2017. The method used in this study is quantitative descriptive. The population in this study was class VII students, amounting to 139 students and the sample in this study was class VII-2, amounting to 30 students. The results showed that the application of the Course Review Horay learning model was very effective because students became more active, enthusiastic and could increase effectiveness in the learning process. Increasing the effectiveness of student learning becomes more effective with the Course Review Horay learning model through postcard media that contains the no tatema mbola dance material. In the postcard there is an explanation of dance movements based on elements of space, time, and energy coupled with pictures of dancers. The application of the Course Review Horay learning model through the postcard media of each group is guided to compete faster in answering questions given by the teacher. The group that succeeds in answering correctly, then the group sings